Video of Colossendeis megalonyx behavior around egg mass - Lobert, Graham; Moran, Amy (IEDA: US Antarctic Program Data Center, 2023)
This video shows the behavior of an adult of Colossendeis megalonyx around a recently-deposited egg mass from a mating group of the same species. The egg mass is indicated by a white circle and label that appears close to the beginning of the video. The adult can be seen manipulating the egg mass with its ovigerous legs (long, with scoop at the end) and palps (shorter). Next to the adult and egg mass are two other Colossendeis in mating posture. The video was taken by Graham Lobert on November 1, 2021 on a GoPro Hero Black at a timelapse rate of one frame per second, played back at 30 fps. The egg mass is approximately three cm across the short diameter.